Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
24 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102449269
Keywords: dept.phy; peer-reviewed

Twin High-Resolution, High-Speed Imagers for the Gemini Telescopes: Instrument Description and Science Verification Results - Scott, Nicholas J.; Howell, Steve B.; Gnilka, Crystal L.; Stephens, Andrew W.; Salinas, Ricardo; Matson, Rachel A.; Furlan, Elise; Horch, Elliott P.; Everett, Mark E.; Ciardi, David R.; Mills, Dave; Quigley, Emmett A. (Frontiers in Astronomy and Space Sciences, 2021)
Two new imaging instruments, ‘Alopeke and Zorro, were designed, built, and commissioned at the Gemini-North and Gemini-South telescopes in 2018 and 2019, respectively. Here we describe them and present the results from over a year of operation. The two identical instruments are based on the legacy of the DSSI (Differential Speckle Survey Instrument) instrument, successfully used for years at the WIYN and the Gemini telescopes in Hawaii and Chile. ‘Alopeke and Zorro are dual-channel imagers having both speckle (6.7″) and “wide-field” (∼1 arcminute) field-of-view options. They were built to primarily perform speckle interferometry providing diffraction-limited imagery at optical wavebands, yielding pixel scale uncertainties of ±0.21 mas, position angle uncertainties of ±0.7◦, and photometric uncertainties of Δm ± 0.02–0.04 magnitudes (for the blue and red channels, respectively) when run through the standard data reduction pipeline. One of their main scientific roles is the validation and characterization of exoplanets and their host stars as discovered by transit surveys such as the NASA Kepler, K2, and TESS missions. The limiting magnitude for speckle observations at Gemini can be quite faint (r ∼18 in good observing conditions) but typically the observed targets are brighter. The instruments can also function as conventional CCD imagers providing a 1 arc-minute field of view and allowing simultaneous two-color, high-speed time-series operation. These resident visitor instruments are remotely operable and are available for use by the community via the peer-reviewed proposal process.
50 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed